Acute Effects of Systemic Erythropoietin Injections on Carotid Body Chemosensory Activity Following Hypoxic and Hypercapnic Stimulation - Andrade, David C.; Iturriaga, Rodrigo; Jeton, Florine; Alcayaga, Julio; Voituron, Nicolas; Del Rio, Rodrigo (My University, 2018)
The carotid body (CB) chemoreceptors sense changes in arterial blood gases. Upon stimulation CB chemoreceptors cells release one or more transmitters to excite sensory nerve fibers of the carotid sinus nerve. While several neurotransmitters have been described to contribute to the CB chemosensory process less is known about modulatory molecules. Recent data suggest that erythropoietin (Epo) is involved in the control of ventilation, and it has been shown that Epo receptor is constitutively expressed in the CB chemoreceptors, suggesting a possible role for Epo in regulation of CB function. Therefore, in the present study we aimed to determine whether exogenous applications of Epo modulate the hypoxic and hypercapnic CB chemosensory responses. Carotid sinus nerve discharge was recorded in-situ from anesthetized adult male and female Sprague Dawley rats (350 g, n = 8) before and after systemic administration of Epo (2000 UI/kg). CB-chemosensitivity to hypoxia and hypercapnia was calculated by exposing the rat to FiO2 5-15% and FiO2 10% gas mixtures, respectively. During baseline recordings at normoxia, we found no effects of Epo on CB activity both in male and female rats. In addition, Epo had no effect on maximal CB response to hypoxia in both male and female rats. Epo injections enhanced the maximum CB chemosensory response to hypercapnia in female rats (before vs. after Epo, 72.5 +/- 7.1 Hz vs. 108.3 +/- 6.9 Hz, p < 0.05). In contrast, Epo had no effect on maximum CB chemosensory response to hypercapnia in male rats but significantly increased the response recovery times (time required to return to baseline discharge following hypercapnic stimulus) from 2.1 +/- 0.1 s to 8.2 +/- 2.3 s (p < 0.05). Taken together, our results suggest that Epo has some modulatory effect on the CB chemosensory response to hypercapnia.
Keywords: carotid body; carotid sinus nerve; erythropoietin; hypoxia; hypercapnia